Protein‐altering variants of PTPN2 in childhood‐onset Type 1A diabetes. Issue 3 (3rd January 2018) - Okuno, M.; Ayabe, T.; Yokota, I.; Musha, I.; Shiga, K.; Kikuchi, T.; Kikuchi, N.; Ohtake, A.; Nakamura, A.; Nakabayashi, K.; Okamura, K.; Momozawa, Y.; et al.
Abstract: Aim: To examine the contribution of PTPN2 coding variants to the risk of childhood‐onset Type 1A diabetes. Methods: PTPN2 mutation analysis was carried out for 169 unrelated Japanese people with childhood‐onset Type 1A diabetes. We searched for coding variants that were absent or extremely rare in the general population and were scored as damaging by multiple in silico programs. We performed mRNA analysis and three‐dimensional structural prediction of the detected variants, when possible. We also examined possible physical links between these variants and previously reported risk SNPs as well as clinical information from variant‐positive children. Results: One frameshift variant (p.Q286Yfs*24) and two probably damaging missense substitutions (p.C232W and p.R350Q) were identified in one child each. Of these, p.Q286Yfs*24 and p.C232W were hitherto unreported, while p.R350Q accounted for 2/121, 122 alleles of the exome datasets. The p.Q286Yfs*24 variant did not encode stable mRNA, and p.C232W appeared to affect the structure of the tyrosine‐protein phosphatase domain. The three variants were physically unrelated to known risk SNPs. The variant‐positive children manifested Type 1A diabetes without additional clinical features and invariably carried risk human leukocyte antigen alleles. Conclusions: The results provide the first indication that PTPN2 variants contribute to the risk of Type 1A diabetes, independently of known risk SNPs. PTPN2 coding variants possibly induce non‐specific Type 1A diabetes phenotypes in individuals with human leukocyte antigen‐mediated disease susceptibility. Our findings warrant further validation. What's new?: Protein‐altering variants in PTPN2 probably constitute novel susceptibility factors for childhood‐onset Type 1A diabetes. PTPN2 variants appear to be physically independent of previously reported risk variants, and may therefore contribute to the missing heritability of Type 1A diabetes. PTPN2 coding variants possibly induce non‐specific phenotypes of Type 1A diabetes in individuals with human leukocyte antigen‐mediated disease susceptibility.